The Black Box of Blame: Can AI Be Held Accountable for Errors? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
Introduction: The Accountability Conundrum in the Age of AI The integration of Artificial Intelligence (AI) into professional sectors, particularly digi...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Machine Learning; Medical Ethics